Laminated body
By designing a transparent conductive layer and a base layer with a specific raised structure in the laminated body, the problems of high resistivity and insufficient adhesion in the prior art are solved, and the effects of low resistivity and excellent adhesion are achieved.
Patent Information
- Application Number
- CN202411340721.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2024-09-25
- Publication Date
- 2025-04-01
AI Technical Summary
During the crystallization process of the transparent conductive layer of the conventional laminate, the crystal orientation is difficult to be consistent, resulting in a higher resistivity; and when the second bulge is not formed, the adhesion between the base layer and the transparent conductive layer is insufficient.
A laminated body is designed, including a base layer and a crystalline transparent conductive layer arranged on one side of the base layer. The transparent conductive layer has a plurality of first bulges having a height of 3 nm or more in thickness, and the same side surface of the base layer has at least one second bulge with a height of 3 nm or more in thickness. The first bulge has a non-repeatable bulge that does not coincide with the second bulge when projected in the thickness direction, and a repeatable bulge that does not coincide with the second bulge.
The lower resistivity of the transparent conductive layer and excellent adhesion to the base layer are achieved, both of which are used.
Smart Images

Figure CN119742105A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminated body. Background Art
[0002] A laminate is known, which includes: a base layer; and a crystalline transparent conductive layer disposed on one side of the base layer (for example, see Patent Document 1 below). In the laminate described in Patent Document 1, one surface of the transparent conductive layer in the thickness direction has a first protrusion. One surface of the base layer in the thickness direction has a second protrusion. When the second protrusion of the base layer is projected in the thickness direction, it overlaps with the first protrusion of the transparent conductive layer.
[0003] In the manufacture of the laminated body of Patent Document 1, a second protrusion corresponding to the shape of the particles is formed on the base layer by coating a resin composition containing particles. In addition, a thin film is formed on one surface in the thickness direction of the base layer, and a first protrusion following the second protrusion is formed on the transparent conductive layer.
[0004] The transparent conductive layer is made crystalline by heating the amorphous transparent conductive layer. However, in the laminate of Patent Document 1, due to the second protrusion, the orientation of the crystals is difficult to be consistent during the crystallization of the amorphous transparent conductive layer, that is, the growth of the crystals is hindered, and thus there is an undesirable condition that the resistivity of the crystallized transparent conductive layer becomes high.
[0005] On the other hand, in order to suppress the increase of resistivity, it has been studied to use a resin composition without particles in the formation of the base layer so as not to form the above-mentioned second protrusions. However, when the second protrusions are not formed, there is a problem that the adhesion between the base layer and the transparent conductive layer is insufficient.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2017-122992 Summary of the invention
[0009] The present invention is a laminate including a transparent conductive layer having both low resistivity and excellent adhesion to an underlayer.
[0010] The present invention [1] includes a laminate comprising: a base layer; and a crystalline transparent conductive layer disposed on one side of the base layer in a thickness direction, the base layer comprising a resin, the surface of the transparent conductive layer on one side in the thickness direction comprising a plurality of first protrusions having a height of 3 nm or more, the surface of the base layer on the one side comprising at least one second protrusion having a height of 3 nm or more, the first protrusion comprising at least one non-repetitive first protrusion that does not overlap with the second protrusion when projected in the thickness direction, and the first protrusion comprising at least one repetitive first protrusion that overlaps with the second protrusion when projected in the thickness direction.
[0011] The present invention [2] includes the stacked body as described in [1] above, wherein the repetitive first protrusions have at least one specific growth type-repetitive first protrusion, and the specific growth type-repetitive first protrusion has a height higher than the height of the second protrusion overlapping when projected in the thickness direction.
[0012] The present invention [3] includes the laminated body described in [1] or [2] above, wherein the material of the transparent conductive layer is indium tin composite oxide.
[0013] Effects of the Invention
[0014] In the laminate of the present invention, the transparent conductive layer has a first protrusion, and the base layer has a second protrusion. In addition, the first protrusion has a non-repetitive first protrusion that does not overlap with the second protrusion when projected in the thickness direction. Therefore, the transparent conductive layer has a low resistivity. In addition, the first protrusion has a repetitive first protrusion that overlaps with the second protrusion when projected in the thickness direction. Therefore, the transparent conductive layer has excellent adhesion to the base layer.
[0015] That is, the laminated body of the present invention includes a transparent conductive layer having both low resistivity and excellent adhesion to the base layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a schematic cross-sectional view of one embodiment of the laminated body of the present invention.
[0017] Figure 2 This is a schematic cross-sectional view of another embodiment of the laminated body of the present invention.
[0018] Figure 3 is a reference cross-sectional view of a stacked body without the non-repetitive first ridge.
[0019] Figure 4 This is a reference cross-sectional view of a stacked body without the second protrusion.
[0020] Figure 5 This is a graph showing the relationship between the amount of oxygen introduced and the resistivity in the reactive sputtering in the first step.
[0021] Description of Reference Numerals
[0022] 3: base layer; 4: transparent conductive layer; 31: one side; 32: second ridge; 42: first ridge; 47: non-repetitive first ridge; 48: repetitive first ridge. DETAILED DESCRIPTION
[0023] 1. One embodiment of a laminate
[0024] Reference Figure 1 One embodiment of the laminated body of the present invention will be described.
[0025] The laminate 1 extends in the plane direction. The plane direction is orthogonal to the thickness direction. The laminate 1 has, for example, a substantially rectangular shape when viewed from above. Observation from above refers to observation along the thickness direction. Specifically, the laminate 1 has a sheet shape. Sheets include films. It should be noted that sheets and films are not strictly distinguished.
[0026] In this embodiment, the laminate 1 includes a substrate layer 2, a substrate layer 3, and a transparent conductive layer 4 in order toward one side in the thickness direction. Specifically, the laminate 1 includes: the substrate layer 2; the substrate layer 3, which is arranged on one side 21 of the substrate layer 2 in the thickness direction; and the transparent conductive layer 4, which is arranged on one side 31 of the substrate layer 3 in the thickness direction. Figure 1 As shown, in this embodiment, two layers adjacent to each other in the thickness direction are adjacent to each other.
[0027] 1.1 Base material layer 2
[0028] The base material layer 2 is arranged on the side of the base layer 3 opposite to the transparent conductive layer 4 in the thickness direction. The base material layer 2 has a sheet shape. The base material layer 2 is preferably transparent.
[0029] As the material of the substrate layer 2, resins can be listed. In other words, the substrate layer 2 contains resins. As resins, polyester resins, acrylic resins, olefin resins, polycarbonate resins, polyethersulfone resins, polyarylate resins, melamine resins, polyamide resins, polyimide resins, cellulose resins, polystyrene resins and norbornene resins can be listed. As resins, preferably, polyester resins can be listed from the viewpoints of transparency and mechanical strength. As polyester resins, for example, polyethylene terephthalate (PET), polybutylene terephthalate and polyethylene naphthalate can be listed, and PET can be preferably listed. The thickness of the substrate layer 2 is, for example, 5 to 500 μm, preferably 10 to 200 μm, and more preferably 10 to 125 μm. In addition, the lower limit of the thickness of the substrate layer 2 is, for example, 5 μm or more, preferably 10 μm or more. In addition, the upper limit of the thickness of the substrate layer 2 is, for example, 500 μm or less, preferably 200 μm or less, and more preferably 125 μm or less.
[0030] The surface 21 in the thickness direction of the substrate layer 2 may have a third protrusion (not shown) with a height of 3 nm or more. The height of the third protrusion (not shown) is required to be the same as the height of the subsequent first protrusion 42. The position and number of the third protrusion (not shown) when viewed from above are not limited.
[0031] The total light transmittance of the substrate layer 2 is, for example, 40% to 100%, preferably 70% to 100%, more preferably 80% to 100%, and further preferably 85% to 100%. In addition, the lower limit of the total light transmittance of the substrate layer 2 is, for example, 40% or more, preferably 70% or more, more preferably 80% or more, and further preferably 85% or more. In addition, the upper limit of the total light transmittance of the substrate layer 2 is, for example, 100% or less. The total light transmittance is determined based on JIS K7375-2008 (the same applies hereinafter).
[0032] 1.2 Base layer 3
[0033] The base layer 3 is disposed on one side of the base material layer 2 in the thickness direction. Figure 1 In the embodiment of the present invention, the base layer 3 is adjacent to one surface of the substrate layer 2. Specifically, the base layer 3 is in contact with one surface 21 of the substrate layer 2 in the thickness direction. The base layer 3 is preferably transparent. Examples of the base layer 3 include an optical adjustment layer and a hard coating layer. The base layer 3 is a single layer (single layer) or multiple layers, preferably a single layer.
[0034] The base layer 3 has, for example, a sheet shape. In addition, the base layer 3 has a protrusion (hereinafter referred to as a second protrusion) 32 on one surface 31 side.
[0035] More specifically, one surface 31 of the base layer 3 includes at least one second protrusion 32 having a height of 3 nm or more and a second flat portion 33 (a portion that does not protrude).
[0036] The second flat portion 33 is a portion on one surface 31 of the base layer 3 where the second protrusion 32 is not formed.
[0037] The second protrusion 32 is a convex portion protruding from the other side toward one side in the thickness direction on one surface 31 of the base layer 3. The number of the second protrusion 32 may be single or multiple. From the viewpoint of adhesion, it is preferred that the number of the second protrusion 32 is multiple. Figure 1 Two second protuberances 32 are shown.
[0038] The shape of the second protrusion 32 is not particularly limited. As an example, Figure 1 A second protuberance 32 in the shape of a hemisphere is shown.
[0039] More specifically, the second protrusion 32 includes, for example, a second protrusion start portion 35 and a second top portion 36. The second protrusion start portion 35 is a portion where the second protrusion 32 starts protruding from the second flat portion 33. The second top portion 36 is a portion located closest to one side in the thickness direction of the base layer 3 (second protrusion 32).
[0040] The height of the second protrusion 32 is measured based on the second protrusion starting portion 35 and the second top portion 36. More specifically, the height of the second protrusion 32 is the length from the top portion to the sagging point when the second top portion 36 is sagging along the thickness direction relative to a line segment obtained by connecting the two second protrusion starting portions 35 to obtain a sagging point. It should be noted that the height of the second protrusion 32 is measured, for example, by observing the cross section of the base layer 3 using a TEM (Transmission Electron Microscope).
[0041] The height of the second protrusion 32 is not particularly limited as long as it is 3 nm or more. For example, the height (average) of the second protrusion 32 is 4 to 50 nm, preferably 5 to 40 nm, more preferably 6 to 30 nm, further preferably 10 to 20 nm, and particularly preferably 13 to 17 nm. In addition, the lower limit of the height (average) of the second protrusion 32 is, for example, 4 nm or more, preferably 5 nm or more, more preferably 6 nm or more, further preferably 10 nm or more, and particularly preferably 13 nm or more. In addition, the upper limit of the height (average) of the second protrusion 32 is, for example, 50 nm or less, preferably 40 nm or less, more preferably 30 nm or less, further preferably 20 nm or less, and particularly preferably 17 nm or less.
[0042] As the material of the base layer 3, for example, resin and particles can be cited. That is, the base layer 3 contains resin and particles. Preferably, the base layer 3 is composed of resin and particles.
[0043] Examples of the resin include polyester resins, acrylic resins, urethane resins, melamine resins, alkyd resins, and silicone resins. If the raw material of the resin is a curable resin, the base layer 3 is formed as a cured film.
[0044] As particles, for example, resin particles and inorganic oxide particles can be listed. As resin particles, for example, acrylic particles can be listed. As inorganic oxide particles, for example, zirconium oxide particles, aluminum oxide particles and silicon dioxide particles can be listed. As particles, preferably inorganic oxide particles can be listed, and more preferably silicon dioxide particles can be listed. The particle size of the particles is, for example, 3 to 100 nm, and preferably 10 to 50 nm. In addition, the lower limit of the particle size of the particles is, for example, 3 nm or more, and preferably 10 nm or more. In addition, the upper limit of the particle size of the particles is, for example, 100 nm or less, and preferably 50 nm or less.
[0045] The method for forming the base layer 3 is not particularly limited. For example, a composition comprising a resin and particles is prepared, and then the resin composition is applied to the base layer 2 and dried. In addition, the resin is cured as needed. Thus, the base layer 3 comprising a resin and particles is formed on one side of the thickness direction of the base layer 2.
[0046] The thickness (average thickness) of the base layer 3 is, for example, 5 to 10000 nm, preferably 10 to 5000 nm. In addition, the lower limit of the thickness (average thickness) of the base layer 3 is, for example, 5 nm or more, preferably 10 nm or more. In addition, the upper limit of the thickness (average thickness) of the base layer 3 is, for example, 10000 nm or less, preferably 5000 nm or less. It should be noted that the thickness of the base layer 3 is the length in the thickness direction of the second flat portion 33. The thickness of the base layer 3 is measured by TEM observation (cross-section observation).
[0047] The total light transmittance of the base layer 3 is, for example, 70% to 100%, preferably 80% to 100%, and more preferably 85% to 100%. The lower limit of the total light transmittance of the base layer 3 is, for example, 70% or more, preferably 80% or more, and more preferably 85% or more. In addition, the upper limit of the total light transmittance of the base layer 3 is, for example, 100% or less.
[0048] In addition, the laminate of the substrate layer 2 and the base layer 3 is sometimes referred to as a substrate 30. That is, the substrate 30 includes the substrate layer 2 and the base layer 3 in this order toward one side in the thickness direction. The substrate 30 is preferably transparent. Therefore, the substrate 30 is sometimes referred to as a transparent substrate 30.
[0049] The surface direction of the substrate 30 includes the direction in which heat shrinkage occurs after the substrate 30 is heated. The heating temperature can be selected according to the heat resistance of the substrate 30. The heat shrinkage rate in the direction in which heat shrinkage occurs is not particularly limited. For example, from the viewpoint of crack resistance, the heat shrinkage rate after heating the substrate 30 at 160°C for 1 hour is, for example, 0.01% to 1.0%, preferably 0.05% to 0.5%. In addition, the lower limit of the above-mentioned heat shrinkage rate is, for example, 0.01% or more, preferably 0.05% or more. In addition, the upper limit of the above-mentioned heat shrinkage rate is, for example, 1.0% or less, preferably 0.5% or less.
[0050] 1.3 Transparent conductive layer 4
[0051] The transparent conductive layer 4 is adjacent to one side of the base layer 3 in the thickness direction. Specifically, the transparent conductive layer 4 is in contact with a surface 31 on one side of the base layer 3 in the thickness direction. The transparent conductive layer 4 forms a surface on one side of the thickness direction of the laminate 1. The transparent conductive layer 4 has a sheet shape extending in the surface direction. In the present embodiment, the transparent conductive layer 4 is a single layer.
[0052] The transparent conductive layer 4 has, for example, a sheet shape. In addition, the transparent conductive layer 4 has a protrusion (hereinafter referred to as a first protrusion) 42 on one surface 41 side.
[0053] More specifically, one surface 41 in the thickness direction of the transparent conductive layer 4 includes a plurality of first protrusions 42 having a height of 3 nm or more and a first flat portion 43 (a portion that does not protrude).
[0054] The first flat portion 43 is a portion on one surface 41 of the transparent conductive layer 4 where the first protrusion 42 is not formed.
[0055] The first protrusions 42 are convex portions that protrude from the other side toward one side in the thickness direction on one surface 41 of the transparent conductive layer 4. The number of the first protrusions 42 is plural. Figure 1 Three first protrusions 42 are shown.
[0056] The shape of the first protrusion 42 is not particularly limited. As an example, Figure 1 A first protuberance 42 in a hemispherical shape is shown in FIG.
[0057] More specifically, the first protrusion 42 includes, for example, a first protrusion start portion 45 and a first top portion 46. The first protrusion start portion 45 is a portion where the first protrusion 42 starts protruding from the first flat portion 43. The first top portion 46 is a portion located closest to one side in the thickness direction of the transparent conductive layer 4 (first protrusion 42).
[0058] The height of the first protrusion 42 is measured based on the first protrusion starting portion 45 and the first top portion 46. More specifically, the height of the first protrusion 42 is the length from the top portion to the sagging point when the first top portion 46 is sagging along the thickness direction relative to a line segment obtained by connecting the two first protrusion starting portions 45 to obtain a sagging point. It should be noted that the height of the first protrusion 42 is measured by observing the cross section of the transparent conductive layer 4 using a TEM, for example.
[0059] The height of the first protrusion 42 is not particularly limited as long as it is greater than 3 nm. For example, the height (average) of the first protrusion 42 is 3 to 50 nm, preferably 4 to 40 nm, more preferably 5 to 30 nm, further preferably 6 to 28 nm, and particularly preferably 7 to 25 nm. In addition, the lower limit of the height (average) of the first protrusion 42 is, for example, greater than 3 nm, preferably greater than 4 nm, more preferably greater than 5 nm, further preferably greater than 6 nm, and particularly preferably greater than 7 nm. In addition, the upper limit of the height (average) of the first protrusion 42 is, for example, less than 50 nm, preferably less than 40 nm, more preferably less than 30 nm, further preferably less than 28 nm, and particularly preferably less than 25 nm.
[0060] The first protrusions 42 are classified into repetitive first protrusions 47 and non-repetitive first protrusions 48 according to whether or not they overlap with the second protrusions 32 in the thickness direction.
[0061] More specifically, as referenced Figure 1 Thus, the first protrusion 42 includes at least one repetitive first protrusion 47 that overlaps with the second protrusion 32 when projected in the thickness direction. In addition, the first protrusion 42 includes at least one non-repetitive first protrusion 48 that does not overlap with the second protrusion 32 when projected in the thickness direction.
[0062] The repetitive first ridges 47 are ridges that overlap with the second ridges 32 in the thickness direction of the laminate 1. That is, in the thickness direction of the laminate 1, the projection surface of the repetitive first ridges 47 has a portion that overlaps with the projection surface of the second ridges 32.
[0063] There is no particular limitation on the method of forming the repetitive first protrusions 47. For example, by forming the transparent conductive layer 4 on one side of the second protrusions 32 by a known method, the repetitive first protrusions 47 corresponding to the shape of the second protrusions 32 can be formed.
[0064] The height of the repetitive first protrusions 47 is not particularly limited as long as it is 3 nm or more. For example, the height of the repetitive first protrusions 47 may be the same as or different from the height of the second protrusions 32 overlapping the repetitive first protrusions in the thickness direction.
[0065] More specifically, when the transparent conductive layer 4 is formed uniformly on one side of the second protrusion 32 in the thickness direction, the repetitive first protrusion 47 is formed by the second protrusion 32 repeated in the thickness direction. Therefore, the height of the second protrusion 32 is substantially the same as the height of the repetitive first protrusion 47. Hereinafter, when the repetitive first protrusion 47 has substantially the same height as the height of the second protrusion 32 that overlaps when projected in the thickness direction, the repetitive first protrusion 47 is sometimes referred to as a uniform-repetitive first protrusion 47A.
[0066] On the other hand, for example, in the case where the crystal growth of the transparent conductive layer 4 grows in a manner protruding in a specific direction, the transparent conductive layer 4 is not uniformly formed on one side of the second protrusion 32 in the thickness direction. In such a case, the repetitive first protrusion 47 is formed by the second protrusion 32 repeated in the thickness direction, and is also formed by crystal growth. That is, the height of the repetitive first protrusion 47 is the sum of the height formed by the second protrusion 32 and the height formed by the growth in a specific direction. As a result, the height of the repetitive first protrusion 47 is higher than the height of the second protrusion 32. Hereinafter, in the case where the repetitive first protrusion 47 has a height higher than the height of the second protrusion 32 that overlaps when projected in the thickness direction, the repetitive first protrusion 47 is sometimes referred to as a specific growth type-repetitive first protrusion 47B.
[0067] From the viewpoint of reducing the resistance value, it is preferable that the repetitive first protrusions 47 include at least one specific growth type-repetitive first protrusion 47B.
[0068] From the viewpoint of damage resistance, it is more preferable that the repetitive first ridges 47 have both uniform-type repetitive first ridges 47A and specific-growth-type repetitive first ridges 47B.
[0069] The height (average) of the specific growth type-repetitive first ridge 47B is higher than the height of the second ridge 32 overlapping with the specific growth type-repetitive first ridge 47B in the thickness direction. The height (average) of the specific growth type-repetitive first ridge 47B is, for example, 4 to 50 nm, preferably 8 to 40 nm, more preferably 10 to 30 nm, further preferably 15 to 28 nm, and particularly preferably 18 to 25 nm. In addition, the lower limit of the height (average) of the specific growth type-repetitive first ridge 47B is, for example, 4 nm or more, preferably 8 nm or more, more preferably 10 nm or more, further preferably 15 nm or more, and particularly preferably 18 nm or more. In addition, the upper limit of the height (average) of the specific growth type-repetitive first ridge 47B is, for example, 50 nm or less, preferably 40 nm or less, more preferably 30 nm or less, further preferably 28 nm or less, and particularly preferably 25 nm or less.
[0070] From the viewpoint of reducing resistivity, the difference (average) between the height (average) of the specific growth type-repetitive first ridge 47B and the height (average) of the second ridge 32 overlapping with the first ridge in the thickness direction is, for example, 1 to 20 nm, preferably 2 to 10 nm, and more preferably 3 to 8 nm. In addition, the lower limit of the difference (average) between the height (average) of the specific growth type-repetitive first ridge 47B and the height (average) of the second ridge 32 is, for example, 1 nm or more, preferably 2 nm or more, and more preferably 3 nm or more. In addition, the upper limit of the difference (average) between the height (average) of the specific growth type-repetitive first ridge 47B and the height (average) of the second ridge 32 is, for example, 20 nm or less, preferably 10 nm or less, and more preferably 8 nm or less.
[0071] The height (average) of the uniform-repetitive first ridge 47A is substantially the same as the height of the second ridge 32 overlapping the uniform-repetitive first ridge 47A in the thickness direction. The height (average) of the uniform-repetitive first ridge 47A is, for example, 4 to 50 nm, preferably 5 to 40 nm, more preferably 6 to 30 nm, further preferably 10 to 20 nm, and particularly preferably 14 to 17 nm. In addition, the lower limit of the height (average) of the uniform-repetitive first ridge 47A is, for example, 4 nm or more, preferably 5 nm or more, more preferably 6 nm or more, further preferably 10 nm or more, and particularly preferably 14 nm or more. In addition, the upper limit of the height (average) of the uniform-repetitive first ridge 47A is, for example, 50 nm or less, preferably 40 nm or less, more preferably 30 nm or less, further preferably 20 nm or less, and particularly preferably 17 nm or less.
[0072] In addition, the height (average) of the uniform-repetitive first ridge 47A may be smaller than the height (average) of the second ridge 32 overlapping in the thickness direction with respect to the uniform-repetitive first ridge 47A. In this case, the difference (average) between the height (average) of the uniform-repetitive first ridge 47A and the height (average) of the second ridge 32 overlapping in the thickness direction with respect to the uniform-repetitive first ridge 47A is, for example, 1 to 20 nm, preferably 2 to 10 nm, and more preferably 3 to 8 nm. In addition, the lower limit of the difference (average) between the height (average) of the uniform-repetitive first ridge 47A and the height (average) of the second ridge 32 overlapping in the thickness direction with respect to the uniform-repetitive first ridge 47A is, for example, 1 nm or more, preferably 2 nm or more, and more preferably 3 nm or more. In addition, the upper limit of the difference (average) between the height (average) of the uniform-repetitive first protrusion 47A and the height (average) of the second protrusion 32 overlapping with the uniform-repetitive first protrusion 47A in the thickness direction is, for example, less than 20 nm, preferably less than 10 nm, and more preferably less than 8 nm.
[0073] In addition, the difference (average) between the height (average) of the uniform-repetitive first ridge 47A and the height (average) of the specific growth type-repetitive first ridge 47B is, for example, 1 to 20 nm, preferably 2 to 10 nm, and more preferably 3 to 8 nm. In addition, the lower limit of the difference (average) between the height (average) of the uniform-repetitive first ridge 47A and the height (average) of the specific growth type-repetitive first ridge 47B is, for example, 1 nm or more, preferably 2 nm or more, and more preferably 3 nm or more. In addition, the upper limit of the difference (average) between the height (average) of the uniform-repetitive first ridge 47A and the height (average) of the specific growth type-repetitive first ridge 47B is, for example, 20 nm or less, preferably 10 nm or less, and more preferably 8 nm or less.
[0074] The non-repeating first protrusions 48 are protrusions that do not overlap with the second protrusions 32 in the thickness direction of the laminate 1. That is, in the thickness direction of the laminate 1, the projection surface of the non-repeating first protrusions 48 does not overlap with the projection surface of the second protrusions 32.
[0075] There is no particular limitation on the method of forming the non-repetitive first protrusions 48. For example, when the transparent conductive layer 4 is formed on one side of the second protrusions 32, the crystal growth of the transparent conductive layer 4 can be controlled by appropriately adjusting the formation conditions to form the non-repetitive first protrusions 48.
[0076] The shape of the non-repetitive first protrusion 48 is not particularly limited. As an example, Figure 1 A non-repeating first ridge 48 in the shape of a hemisphere is shown.
[0077] There is no particular limitation on the height of the non-repetitive first ridge 48 as long as it is greater than 3 nm. For example, the height of the non-repetitive first ridge may be the same as or different from the height of the above-mentioned repetitive first ridge. For example, the height of the non-repetitive first ridge 48 is 3 to 40 nm, preferably 4 to 30 nm, more preferably 5 to 20 nm, further preferably 6 to 15 nm, and particularly preferably 7 to 13 nm. In addition, the lower limit of the height of the non-repetitive first ridge 48 is greater than 3 nm, preferably greater than 4 nm, more preferably greater than 5 nm, further preferably greater than 6 nm, and particularly preferably greater than 7 nm. In addition, the upper limit of the height of the non-repetitive first ridge 48 is less than 40 nm, preferably less than 30 nm, more preferably less than 20 nm, further preferably less than 15 nm, and particularly preferably less than 13 nm.
[0078] The method for forming the transparent conductive layer 4 is not particularly limited. For example, a metal oxide is sputtered onto the base layer 3 and the sputtered metal oxide is heated. Thus, the transparent conductive layer 4 containing the metal oxide is formed on one side of the base layer 3 in the thickness direction.
[0079] The metal oxide contains, for example, at least one metal selected from the group consisting of In, Sn, Zn, Ga, Sb, Nb, Ti, Si, Zr, Mg, Al, Au, Ag, Cu, Pd, and W.
[0080] More specifically, as the material of the transparent conductive layer 4, preferably, there can be mentioned: indium zinc composite oxide (IZO), indium gallium zinc composite oxide (IGZO), indium gallium composite oxide (IGO), indium tin composite oxide (ITO) and antimony tin composite oxide (ATO). From the viewpoint of reducing the resistivity, indium tin composite oxide (ITO) is preferably mentioned. That is, from the viewpoint of reducing the resistivity, it is preferred that the material of the transparent conductive layer 4 is indium tin composite oxide (ITO).
[0081] The content of tin oxide (SnO2) in the indium tin composite oxide is, for example, 0.5 mass% or more, preferably 3 mass% or more, more preferably 6 mass% or more, and, for example, less than 50 mass%, preferably 25 mass% or less, more preferably 15 mass% or less.
[0082] The sputtering conditions and the heating conditions are appropriately adjusted so as to form the repetitive first ridges 47 and the non-repetitive first ridges 48. The details of the sputtering conditions and the heating conditions will be described later.
[0083] In addition, the transparent conductive layer 4 is crystalline. Preferably, the transparent conductive layer 4 does not contain an amorphous region. Preferably, the transparent conductive layer 4 is composed of only a crystalline region.
[0084] It should be noted that, for example, the following test can be used to determine whether the transparent conductive layer 4 is crystalline or amorphous. After the transparent conductive layer 4 is immersed in a 5 mass % hydrochloric acid aqueous solution for 15 minutes, it is washed with water and dried, and the resistance between the two terminals of about 15 mm on one side 41 of the transparent conductive layer 4 is measured. If the resistance between the two terminals is 10 kΩ or less, the transparent conductive layer 4 is crystalline, and if the resistance between the two terminals exceeds 10 kΩ, the transparent conductive layer 4 is amorphous. The crystalline transparent conductive layer 4 can sufficiently reduce the resistivity.
[0085] The thickness (average thickness) of the transparent conductive layer 4 is, for example, 15 to 500 nm, preferably 35 to 400 nm, more preferably 50 to 300 nm, further preferably 75 to 200 nm, further preferably 80 to 200 nm, further preferably 85 to 200 nm, further preferably 90 to 200 nm, particularly preferably 100 to 200 nm, and particularly preferably 120 to 200 nm. In addition, the lower limit of the thickness (average thickness) of the transparent conductive layer 4 is, for example, 15 nm or more, preferably 35 nm or more, more preferably 50 nm or more, further preferably 75 nm or more, further preferably 80 nm or more, further preferably 85 nm or more, further preferably 90 nm or more, particularly preferably 100 nm or more, and particularly preferably 120 nm or more. In addition, the upper limit of the thickness (average thickness) of the transparent conductive layer 4 is, for example, 500 nm or less, preferably 400 nm or less, more preferably 300 nm or less, further preferably 200 nm or less, further preferably 200 nm or less, further preferably 200 nm or less, further preferably 200 nm or less, particularly preferably 200 nm or less, and particularly preferably 200 nm or less. It should be noted that the thickness of the transparent conductive layer 4 (average thickness) is the length in the thickness direction of the first flat portion 43. The thickness of the transparent conductive layer 4 is measured, for example, by TEM observation (cross-section observation).
[0086] In particular, from the viewpoint of forming the non-repetitive first ridges 48, the lower limit of the thickness (average thickness) of the transparent conductive layer 4 is preferably 35 nm or more, more preferably 50 nm or more, and even more preferably 75 nm or more. Furthermore, from the viewpoint of forming the specific growth type-repetitive first ridges, the lower limit of the thickness (average thickness) of the transparent conductive layer 4 is even more preferably 80 nm or more, even more preferably 85 nm or more, even more preferably 90 nm or more, even more preferably 100 nm or more, and particularly preferably 120 nm or more.
[0087] It should be noted that the thickness (average thickness) of the transparent conductive layer 4 can be arbitrarily adjusted by, for example, appropriately setting a sputtering time of sputtering described later.
[0088] The total light transmittance of the transparent conductive layer 4 is, for example, 60% to 100%, preferably 80% to 100%, and more preferably 85% to 100%. In addition, the lower limit of the total light transmittance of the transparent conductive layer 4 is, for example, 60% or more, preferably 80% or more, and more preferably 85% or more. The upper limit of the total light transmittance of the transparent conductive layer 4 is, for example, 100% or less.
[0089] The resistivity of one surface 41 of the transparent conductive layer 4 in the thickness direction is, for example, 3.0×10 -4 ~0.1×10 -4 Ω·cm, preferably 2.5×10 -4 ~0.5×10 -4 Ω·cm, more preferably 2.3×10 -4 ~1.0×10 -4 Ω·cm, more preferably 2.2×10 -4 ~1.1×10 -4 Ω·cm, particularly preferably 2.0×10 -4 ~1.1×10 -4 Ω·cm, particularly preferably 1.9×10 -4 ~1.1×10 -4 Ω·cm. The lower limit of the resistivity of the surface 41 of the transparent conductive layer 4 in the thickness direction is, for example, 0.1×10 -4 Ω·cm or more, preferably 0.5×10 -4 Ω·cm or more, more preferably 1.0×10 -4 Ω·cm or more, more preferably 1.1×10 -4 Ω·cm or more. The upper limit of the resistivity of the surface 41 of the transparent conductive layer 4 in the thickness direction is, for example, 3.0×10 -4 Ω·cm or less, preferably 2.5×10 -4 Ω·cm or less, more preferably 2.3×10 -4 Ω·cm or less, more preferably 2.2×10 -4 Ω·cm or less, particularly preferably 2.0×10 -4 Ω·cm or less, particularly preferably 1.9×10 -4 The resistivity was measured by a four-terminal method.
[0090] Next, a method for producing the laminated body 1 will be described. In this method, each layer is arranged by a roll-to-roll method.
[0091] First, a long base material layer 2 is prepared.
[0092] Next, the resin composition containing the resin and particles is applied to one side 21 of the substrate layer 2. Then, when the resin composition contains a curable resin, the curable resin is cured by heat or ultraviolet irradiation. Thus, a substrate layer 3 having a second protrusion 32 is formed. In addition, a substrate 30 having a substrate layer 2 and a substrate layer 3 in sequence on one side in the thickness direction is manufactured.
[0093] Then, the transparent conductive layer 4 is formed on one surface 31 in the thickness direction of the base layer 3. The method of forming the transparent conductive layer 4 includes, for example, a first step and a second step.
[0094] In the first step, an amorphous transparent conductive layer 40 is formed on one surface 31 in the thickness direction of the base layer 3. The amorphous transparent conductive layer 40 is formed on one surface 31 in the thickness direction of the base layer 3 by, for example, sputtering (preferably reactive sputtering).
[0095] A sputtering device is used for sputtering. The sputtering device includes a film-forming roller. The film-forming roller includes a cooling device. The cooling device can cool the film-forming roller. The film-forming roller can cool the base layer 3 (the base material 30 including the base layer 3).
[0096] In sputtering (preferably reactive sputtering), the above-mentioned metal oxide (sintered body) is used as a target. The surface temperature of the film-forming roller corresponds to the film-forming temperature of sputtering.
[0097] From the viewpoint of forming the first protrusions 42 , the film forming temperature is, for example, -50 to 10.0°C, preferably -20 to 0.0°C, more preferably -10 to -2.5°C, further preferably -10 to -5.0°C, and particularly preferably -10 to -7.0°C.
[0098] In particular, from the viewpoint of forming the non-repetitive first protrusions 48 , the upper limit of the film forming temperature is, for example, 10.0° C. or less, preferably 0.0° C. or less, more preferably −2.5° C. or less, further preferably −5.0° C. or less, and further preferably −7.0° C. or less.
[0099] From the viewpoint of forming the specific growth type-repetitive first ridges 47 , the lower limit of the film formation temperature is, for example, −50° C. or higher, preferably −20° C. or higher, and more preferably −10° C. or higher.
[0100] As the sputtering gas, for example, a rare gas can be mentioned. As the rare gas, for example, Ar and Kr can be mentioned. The sputtering gas can be mixed with a reactive gas. As the reactive gas, for example, oxygen can be mentioned.
[0101] From the perspective of forming the first protrusion 42, the ratio of the introduction amount of the reactive gas to the total introduction amount of the sputtering gas and the reactive gas is, for example, 0.1 to 5% of the flow rate, preferably 0.5 to 5% of the flow rate, more preferably 1.5 to 3% of the flow rate, further preferably 2.0 to 3% of the flow rate, and particularly preferably 2.5 to 3% of the flow rate.
[0102] In particular, from the perspective of forming a non-repetitive first protrusion 48, the lower limit of the ratio of the introduction amount of the reactive gas to the total introduction amount of the sputtering gas and the reactive gas is, for example, greater than 0.1 flow%, preferably greater than 0.5 flow%, more preferably greater than 1.5 flow%, further preferably greater than 2.0 flow%, and particularly preferably greater than 2.5 flow%.
[0103] Furthermore, from the viewpoint of forming the specific growth type-repetitive first protrusions 47 , the upper limit of the ratio of the introduction amount of the reactive gas to the total introduction amount of the sputtering gas and the reactive gas is, for example, 5 flow % or less, preferably 3 flow % or less.
[0104] The amorphous transparent conductive layer 40 formed in the first step may not have the first protrusions 42 at the stage before being provided to the second step, or may already have the first protrusions 42 .
[0105] In the second step, the amorphous transparent conductive layer 40 is crystallized to form the crystalline transparent conductive layer 4. Specifically, in the second step, the amorphous transparent conductive layer 40 is heated. The heating is performed in, for example, an air atmosphere.
[0106] From the viewpoint of forming the first protrusions 42 , the heating temperature is, for example, 80 to 200°C, preferably 110 to 180°C, more preferably 150 to 175°C, and further preferably 150 to 170°C.
[0107] In particular, from the viewpoint of forming the non-repetitive first protrusions 48 , the lower limit of the heating temperature is, for example, 80° C. or higher, preferably 110° C. or higher, more preferably 130° C. or higher, and further preferably 150° C. or higher.
[0108] From the viewpoint of forming the specific growth type-repetitive first protrusions 47 , the upper limit of the heating temperature is, for example, 200° C. or lower, preferably 180° C. or lower, more preferably 175° C. or lower, and further preferably 170° C. or lower.
[0109] From the viewpoint of forming the first protrusions 42 , the heating time is, for example, 1 minute to 25 hours, preferably 3 minutes to 5 hours, and more preferably 5 minutes to 2 hours.
[0110] In particular, from the viewpoint of forming the non-repetitive first protrusions 48 , the lower limit of the heating time is, for example, 1 minute or more, preferably 3 minutes or more, and more preferably 5 minutes or more.
[0111] From the viewpoint of forming the specific growth type-repetitive first protrusions 47 , the upper limit of the heating time is, for example, 15 hours or less, preferably 5 hours or less, more preferably 3 hours or less, and further preferably 2 hours or less.
[0112] In this way, the laminated body 1 including the base material layer 2 , the underlayer 3 , and the transparent conductive layer 4 in this order toward one side in the thickness direction can be manufactured.
[0113] The total light transmittance of the laminate 1 is, for example, 50% to 100%, preferably 70% to 100%, more preferably 80% to 100%, and further preferably 85% to 100%. In addition, the lower limit of the total light transmittance of the laminate 1 is, for example, 50% or more, preferably 70% or more, more preferably 80% or more, and further preferably 85% or more. In addition, the upper limit of the total light transmittance of the laminate 1 is, for example, 100% or less.
[0114] 2. Application of the laminate 1
[0115] The laminate 1 is used, for example, for articles. Specifically, the laminate 1 is an optical laminate, and examples of the articles include optical articles. Specifically, examples of the articles include touch sensors, electromagnetic wave shielding parts, dimming elements, photoelectric conversion elements, heat ray control components, light-transmitting antenna components, light-transmitting heater components, image display devices, and lighting.
[0116] 3. Effects of an Implementation Method
[0117] For example, as referenced Figure 3 In this way, in the laminate 1, when the base layer 3 has the second protrusions 32, the transparent conductive layer 4 is usually formed following the second protrusions 32 and has the repetitive first protrusions 47. On the other hand, the non-repetitive first protrusions 48 may not be formed depending on the formation conditions of the transparent conductive layer 4. In such a case, the resistance value of the transparent conductive layer 4 may become higher.
[0118] In addition, as referenced Figure 4 In this way, in the laminated body 1 , when the base layer 3 does not have the second protrusions 32 , the transparent conductive layer 4 does not have excellent adhesion to the base layer 3 .
[0119] In contrast to these situations, such as reference Figure 1In this way, the laminate 1 has both the first protrusion 42 and the second protrusion 32. That is, the transparent conductive layer 4 has the first protrusion 42, and the base layer 3 has the second protrusion 32. In addition, the first protrusion 42 has the non-repetitive first protrusion 48 that does not overlap with the second protrusion 32 when projected in the thickness direction. Therefore, the transparent conductive layer 4 has a low resistivity. In addition, the first protrusion 42 has the repetitive first protrusion 47 that overlaps with the second protrusion 32 when projected in the thickness direction. Therefore, the transparent conductive layer 4 has excellent adhesion to the base layer 3.
[0120] That is, the laminated body 1 described above includes the transparent conductive layer 4 having both low resistivity and excellent adhesion to the base layer 3 .
[0121] Furthermore, when the first protrusions 42 and the second protrusions 32 are formed, excellent scratch resistance can be obtained in each step when manufacturing the laminated body 1 .
[0122] In the above-mentioned laminated body 1, the repetitive first ridges 47 preferably include at least one specific growth type-repetitive first ridge 47B. The specific growth type-repetitive first ridges 47 have a height higher than the height of the second ridges 32 overlapping when projected in the thickness direction.
[0123] When such specific growth type-repetitive first protrusions 47B are formed, particularly excellent scratch resistance can be obtained in each step when manufacturing the laminated body 1 .
[0124] Furthermore, in the above-mentioned laminated body 1, when the material of the transparent conductive layer 4 is indium tin composite oxide, the above-mentioned laminated body 1 has excellent productivity, resistivity, and transparency.
[0125] 4. Modifications
[0126] like Figure 1As shown by the imaginary line in the middle, the laminate 1 may have other layers 5 as needed. As other layers 5, for example, functional layers may be listed, and more specifically, dimming functional layers may be listed. As dimming functional layers, for example, voltage-driven dimming coatings and current-driven dimming coatings may be listed. The dimming functional layer is used, for example, in polymer dispersed liquid crystals (PDLC), polymer network liquid crystals (PNLC), suspended particle devices (SPD: suspended particle device) and electrochromic (EC: Electrochromic). In addition, as a functional layer, for example, a metal functional layer obtained using a metal paste may be listed. As metals, for example, silver, copper and titanium may be listed. In addition, as far as the functional layer is concerned, it can be selected as needed in the manufacture of the above-mentioned articles (such as touch sensors, electromagnetic wave shielding parts, dimming elements, photoelectric conversion elements, heat ray control components, translucent antenna components, translucent heater components, image display devices and lighting) using the laminate 1, and can be formed arbitrarily at an appropriate position and time.
[0127] The other layer 5 is disposed, for example, by a known method on one surface in the thickness direction of the laminate 1. Preferably, the other layer 5 is disposed by a known method on one surface 41 in the thickness direction of the transparent conductive layer 4. In addition, preferably, the other layer 5 is adjacent to one surface 41 in the thickness direction of the transparent conductive layer 4.
[0128] In addition, as referenced Figure 2 In this way, the repetitive first ridges 47 may include only the uniform type repetitive first ridges 47A without the specific growth type repetitive first ridges 47B. From the viewpoint of damage resistance, it is preferable that, as shown in FIG. Figure 1 In this way, the repetitive first ridges 47 include uniform-repetitive first ridges 47A and specific-growth-repetitive first ridges 47B.
[0129] Although not shown, the laminate 1 may not include the base layer 2. In this case, the laminate 1 may include only the base layer 3 and the transparent conductive layer 4. The laminate 1 may include only the base layer 3, the transparent conductive layer 4, and the other layer 5.
[0130] In addition, in the above description, reference is made to Figure 1 , an embodiment in which the base layer 3 is adjacent to the crystalline transparent conductive layer 4 is described in detail. However, the base layer and the transparent conductive layer 4 may not be adjacent. For example, although not shown in the figure, a transparent inorganic layer may be arranged between the base layer 3 and the transparent conductive layer 4.
[0131] The transparent inorganic layer is, for example, an oxide, a nitride and a nitride oxide of a known inorganic element. Examples of the inorganic element include silicon, niobium, zirconium, zinc, titanium, aluminum, gallium and tin. The transparent inorganic layer may have a stoichiometric composition or a non-stoichiometric composition. In addition, in the transparent inorganic layer, the type of inorganic element may be one or more. In addition, the transparent inorganic layer may be a single layer or a multilayer (laminated layer). In addition, the transparent inorganic layer may be a single film continuous in the surface direction, or a discontinuous film having an island structure. In addition, the thickness of the transparent inorganic layer may be, for example, 0.1 to 300 nm, preferably 0.1 to 150 nm. In addition, the lower limit of the thickness of the transparent inorganic layer may be, for example, more than 0.1 nm. In addition, the upper limit of the thickness of the transparent inorganic layer may be, for example, less than 300 nm, preferably less than 150 nm.
[0132] [Example]
[0133] Hereinafter, embodiments and comparative examples are shown to further specifically describe the present invention. It should be noted that the present invention is not limited to any embodiments and comparative examples. In addition, the specific numerical values such as the mixing ratio (containing ratio), physical property values, and parameters used in the following description can be replaced by the upper limit (defined as "below", "less than") or lower limit (defined as "above", "exceeding") of the corresponding recordings of the mixing ratio (containing ratio), physical property values, and parameters described in the above-mentioned "specific embodiments" and corresponding to them.
[0134] Example 1
[0135] A substrate layer formed of a long PET film (thickness 125 μm, manufactured by MITSUBISHI CHEMICAL CO., LTD.) was prepared.
[0136] Furthermore, a thermosetting resin composition containing a polyester resin and silica particles (particle diameter 25 nm) was prepared.
[0137] Next, a thermosetting resin was applied to one surface in the thickness direction of the base material layer to obtain a coating film.
[0138] Next, the coating film is heated and dried to solidify the coating film to form a base layer. The thickness of the base layer is about 10 nm. Thus, a base material having a base layer and a base layer in sequence in the thickness direction is obtained.
[0139] Next, an amorphous transparent conductive layer is formed on one surface of the base layer in the thickness direction.
[0140] As a method for forming the transparent conductive layer, a reactive sputtering method was used. In the reactive sputtering method, a DC (Direct Current) magnetron sputtering device was used. The sputtering method and conditions are as follows.
[0141] That is, a DC power supply is used to apply a voltage to the target of the following (1). In this method, the horizontal magnetic field intensity on the target is adjusted to the value of the following (2).
[0142] In this method, the film forming temperature is adjusted to the value of (3) below. It should be noted that the film forming temperature is the surface temperature of the film forming roller. The film forming temperature is the same as the temperature of the substrate (the laminate of the substrate layer and the base layer).
[0143] In this method, the film forming chamber of the DC magnetron sputtering device is evacuated. At this time, the ultimate vacuum degree in the film forming chamber is adjusted to the value of the following (4).
[0144] Next, in this method, Ar as a sputtering gas and oxygen as a reactive gas are introduced into the film forming chamber. The ratio of the amount of reactive gas (oxygen) introduced to the total amount of the sputtering gas (Ar) and the reactive gas (oxygen) introduced is adjusted to the value of (5) below. In addition, in this method, the gas pressure in the film forming chamber when the gas is introduced is adjusted to the value of (6) below.
[0145] In this method, the amount of reactive gas (oxygen) introduced is adjusted to the resistivity-oxygen introduction amount curve (refer to Figure 5 ) in region R. In addition, the amount of reactive gas (oxygen) introduced is adjusted so that the resistivity of the amorphous transparent conductive layer is set to the value of (7) below.
[0146] It should be noted that Figure 5 The resistivity-oxygen introduction amount curve shown in is prepared by previously measuring the relationship between the resistivity of the amorphous transparent conductive layer and the oxygen introduction amount when the amorphous transparent conductive layer is formed by a reactive sputtering method.
[0147] Next, the amorphous transparent conductive layer is heated in a hot air oven to be crystallized. The heating temperature is the value of (8) below. In addition, the heating time is the value of (9) below. Thus, a laminate having a substrate layer, a base layer, and a crystalline transparent conductive layer in sequence on one side in the thickness direction is manufactured (see Figure 1 ).
[0148] In the above method, the sputtering time is adjusted so that the thickness of the transparent conductive layer (the thickness measured by FE-TEM observation described later) becomes the value of the following (10).
[0149] <Sputtering conditions>
[0150] (1) Target: a sintered body of indium oxide and tin oxide (tin oxide concentration: 10% by mass).
[0151] (2) Horizontal magnetic field strength on the target: 90 mT (DC power supply).
[0152] (3) Film forming temperature (surface temperature of film forming roller): -8°C.
[0153] (4) Vacuum degree in the film forming chamber before gas introduction: 0.6×10 -4 Pa.
[0154] (5) Ratio of the amount of reactive gas (oxygen) introduced to the total amount of sputtering gas (Ar) and reactive gas (oxygen) introduced: about 2.6% by flow rate.
[0155] (6) Gas pressure in the film-forming chamber when gas is introduced: 0.4 Pa.
[0156] (7) Resistivity of amorphous transparent conductive layer: 6.4×10 -4 Ω·cm.
[0157] (8) Heating temperature: 160°C.
[0158] (9) Heating time: 1 hour.
[0159] (10) Thickness of transparent conductive layer: 145 nm.
[0160] According to the "cross-sectional observation" described later, the cross-sectional state of the laminate was confirmed by a transmission electron microscope (FE-TEM, Field Emission Transmission Electron Microscope: field emission transmission electron microscope). Figure 1 In that way, the laminated body has the first protrusion and the second protrusion.
[0161] That is, in the laminate, the base layer has a plurality of second protrusions, and the height of the second protrusions is about 15 nm.
[0162] In addition, the transparent conductive layer has a plurality of first protrusions.
[0163] More specifically, the first ridges have a plurality of non-repeating first ridges that do not overlap with the second ridges in the thickness direction. The height of the non-repeating first ridges is about 12 nm.
[0164] In addition, the first protrusion has a plurality of repetitive first protrusions that overlap with the second protrusion in the thickness direction. In particular, the repetitive first protrusions have a plurality of uniform-repetitive first protrusions (repetitive first protrusions that do not have a height higher than the height of the second protrusion that overlaps when projected in the thickness direction). The height of the uniform-repetitive first protrusion is about 15 nm.
[0165] Furthermore, the repetitive first ridges have a plurality of specific growth type-repetitive first ridges (repetitive first ridges having a height higher than the height of the second ridges overlapping when projected in the thickness direction). The height of the specific growth type-repetitive first ridges is about 21 nm.
[0166] Example 2
[0167] The sputtering time was changed so that the thickness of the transparent conductive layer would be 75 nm. A laminate was produced in the same manner as in Example 1 except for the above.
[0168] According to the "cross-sectional observation" described later, the cross-sectional state of the laminate was confirmed by transmission electron microscopy (FE-TEM). Figure 2 In that way, the laminated body has the first protrusion and the second protrusion.
[0169] That is, in the laminate, the base layer has a plurality of second protrusions, and the height of the second protrusions is about 15 nm.
[0170] In addition, the transparent conductive layer has a plurality of first protrusions.
[0171] More specifically, the first ridges have a plurality of non-repeating first ridges that do not overlap with the second ridges in the thickness direction. The height of the non-repeating first ridges is about 8 nm.
[0172] In addition, the first protrusion has a plurality of repetitive first protrusions that overlap with the second protrusion in the thickness direction. In particular, the repetitive first protrusions have a plurality of uniform-repetitive first protrusions (repetitive first protrusions that do not have a height higher than the height of the second protrusion that overlaps when projected in the thickness direction). The height of the uniform-repetitive first protrusion is about 15 nm.
[0173] However, the repetitive first ridges do not have a specific growth type - repetitive first ridges (repetitive first ridges having a height higher than the height of the second ridges that overlap when projected in the thickness direction).
[0174] Comparative Example 1
[0175] The sputtering time was changed so that the thickness of the transparent conductive layer was 32 nm. In addition, the film formation temperature was changed to 80° C. Except for this, a laminate was produced in the same manner as in Example 1.
[0176] According to the "cross-sectional observation" described later, the cross-sectional state of the laminate was confirmed by transmission electron microscopy (FE-TEM). Figure 3 In that way, the laminated body has the first protrusion and the second protrusion.
[0177] That is, in the laminate, the base layer has a plurality of second protrusions, and the height of the second protrusions is about 15 nm.
[0178] In addition, the transparent conductive layer has a plurality of first protrusions.
[0179] However, the first protrusion does not have a non-repeating first protrusion that does not overlap with the second protrusion in the thickness direction.
[0180] On the other hand, the first protrusion has a plurality of repetitive first protrusions that overlap with the second protrusion in the thickness direction. In addition, the repetitive first protrusion has a plurality of uniform-repetitive first protrusions (repetitive first protrusions that do not have a height higher than the height of the second protrusion that overlaps when projected in the thickness direction). The height of the uniform-repetitive first protrusion is about 15nm.
[0181] However, the repetitive first protrusions do not have a specific growth type - repetitive first protrusions (repetitive first protrusions having a height higher than the height of the second protrusions that overlap when projected in the thickness direction).
[0182] Comparative Example 2
[0183] In forming the base layer, a thermosetting resin composition containing a polyester resin and not containing silica particles was used. A laminate was produced in the same manner as in Example 1 except for the above.
[0184] According to the "cross-sectional observation" described later, the cross-sectional state of the laminate was confirmed by transmission electron microscopy (FE-TEM). Figure 4 In that way, the laminate has the first protrusions and does not have the second protrusions.
[0185] That is, in the laminated body, the transparent conductive layer has a plurality of first protrusions.
[0186] More specifically, the first ridges have a plurality of non-repeating first ridges that do not overlap with the second ridges in the thickness direction. The height of the non-repeating first ridges is about 12 nm.
[0187] Furthermore, the first ridges do not have repetitive first ridges that overlap with second ridges in the thickness direction.
[0188] <Evaluation>
[0189] The transparent conductive layers of the respective Examples and Comparative Examples were evaluated for the following items.
[0190] [Thickness of transparent conductive layer]
[0191] The thickness of the transparent conductive layer was measured by FE-TEM observation.
[0192] More specifically, first, a sample for cross-sectional observation of the transparent conductive layer was prepared by the FIB microsampling method. In the FIB microsampling method, a FIB apparatus (trade name "FB2200", manufactured by Hitachi) was used. In addition, the acceleration voltage was set to 10 kV.
[0193] Next, the thickness of the transparent conductive layer in the cross-sectional observation sample was measured by FE-TEM observation (cross-sectional observation). In the FE-TEM observation, a FE-TEM apparatus (trade name "JEM-2800", manufactured by JEOL) was used. The acceleration voltage was set to 200 kV.
[0194] [Cross-section observation]
[0195] After adjusting the cross section of the transparent conductive laminate of each example and each comparative example by FIB microsampling method, the cross section of each base layer and transparent conductive layer was observed by FE-TEM to confirm the presence of each of the first protrusion and the second protrusion.
[0196] The number of first protrusions existing in a length of 1 μm on one surface in the thickness direction of the transparent conductive layer was counted. The observation magnification was set so that the presence and height of the first and second protrusions could be observed.
[0197] The apparatus and measurement conditions are as follows.
[0198] FIB apparatus: FB2200 manufactured by Hitachi, accelerating voltage: 10 kV.
[0199] FE-TEM apparatus: JEM-2800 manufactured by JEOL, accelerating voltage: 200 kV.
[0200] [Resistance characteristics]
[0201] The resistance value was measured by a four-terminal method in accordance with JIS K7194 (1994).
[0202] Then, the resistance characteristics were evaluated according to the following criteria.
[0203] ◎: Less than 15.0Ω / □.
[0204] ○: 15.0Ω / □ or more and less than 25.0Ω / □.
[0205] △: 25.0Ω / □ or more and less than 35.0Ω / □.
[0206] ×: 35.0Ω / □ or more.
[0207] [Damage resistance]
[0208] The damage resistance is evaluated by the following method. That is, a sample film (10 cm in MD direction × 5 cm in TD direction) is cut out from the laminate. Then, the transparent substrate side of the sample film is bonded to the glass plate via a double-sided strong adhesive tape. Then, the glass plate with the sample film is set on the workbench of a sliding tester (trade name "10-type pen tester", manufactured by MTM Co., Ltd.). Then, a sliding test is performed on the transparent conductive layer of the sample film on the glass plate by the sliding tester. Specifically, after ethanol is dripped on the transparent conductive layer of the sample film, for the dripping part, the wiper as a sliding member is pressed with a load of 2 kg, and the wiper is reciprocated 100 times in the MD direction (alcohol sliding test). Then, the test object is visually observed to confirm whether the transparent conductive layer is damaged.
[0209] Then, the scratch resistance was evaluated according to the following criteria.
[0210] ◎: No damage was visually confirmed.
[0211] ○: Damage was visually confirmed, and the number of damages was 3 or less.
[0212] △: Damage was visually confirmed, and the number of damages was more than 3 and 6 or less.
[0213] ×: Damage was visually confirmed, and the number of damages exceeded 6.
[0214] [Adhesion]
[0215] Adhesion (adhesion in a humidified environment) was evaluated by the following method: 5 sheets (5 test pieces) of 5 cm x 5 cm laminated bodies were placed in a humidified oven at 85°C and 85% and exposed to the environment for 500 hours. Adhesion was then evaluated in accordance with JIS K5600-5-6 (1999).
[0216] Then, the adhesion was evaluated based on the following criteria.
[0217] ○: All five test subjects meet the category 0, or three or more test subjects meet the category 0 and two or less test subjects meet the category 1.
[0218] ×: Equivalent to a result that does not satisfy the criterion of 0.
[0219] [Table 1]
[0220]
Claims
1. A laminate, wherein: The laminated body comprises: basal layer; and A crystalline transparent conductive layer is disposed on one side of the base layer in the thickness direction. The base layer comprises a resin, The transparent conductive layer has a plurality of first protrusions with a height of 3 nm or more on one surface in the thickness direction. The one surface of the base layer has at least one second protrusion with a height of 3 nm or more, The first protrusion has at least one non-repetitive first protrusion which does not overlap with the second protrusion when projected in the thickness direction. Furthermore, the first protrusion has at least one repetitive first protrusion that overlaps with the second protrusion when projected in the thickness direction.
2. The laminate according to claim 1, wherein The repetitive first protrusion has at least one specific growth type-repetitive first protrusion, The specific growth type-repetitive first protrusion has a height higher than a height of the second protrusion overlapped when projected in the thickness direction.
3. The laminate according to claim 1, wherein The material of the transparent conductive layer is indium tin composite oxide.
4. The laminate according to claim 2, wherein: The material of the transparent conductive layer is indium tin composite oxide.
Citation Information
Patent Citations
Transparent conductive film
JP2017122992A